Spelling mistakes in writing by Indonesian speakers in Timor Leste and their implications - Alowisia Since; Ida Widia; Mochamad Whilky Rizkyanfi (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to analyze spelling errors in descriptive essays written by BIPA (Indonesian for Foreign Speakers) students in Timor Leste and their implications for the development of teaching materials. Writing is a crucial productive skill, yet BIPA students often face difficulties with writing conventions, primarily due to first-language interference and limited morphological understanding. Using a descriptive qualitative approach, this research analyzed descriptive essays from eleventh-grade students at SMA Nino Koni Santana Gleno. Data was collected through document studies, observation, and interviews to identify, classify, and interpret errors. The analysis revealed that errors in writing prepositions were the most dominant, followed by errors in affixed words, basic words, and reduplicated words. This finding indicates that students face fundamental difficulties in distinguishing between prepositions and prefixes. This finding highlights the importance of developing teaching materials that focus on students' specific errors, provide structured exercises, and integrate learners' cultural contexts to enhance accuracy and linguistic awareness. Therefore, a focused pedagogical intervention is needed to bridge the gap between vocabulary mastery and the correct application of spelling rules. Abstrak Penelitian ini bertujuan untuk menganalisis kesalahan ejaan pada karangan deskriptif peserta didik BIPA (Bahasa Indonesia bagi Penutur Asing) di Timor Leste dan implikasinya terhadap pengembangan bahan ajar. Menulis merupakan keterampilan produktif yang krusial, namun peserta didik BIPA sering menghadapi kesulitan terkait kaidah penulisan, terutama karena interferensi bahasa pertama dan pemahaman morfologi yang terbatas. Menggunakan pendekatan kualitatif deskriptif, penelitian ini menganalisis karangan deskriptif dari peserta didik kelas XI di SMA Nino Koni Santana Gleno. Pengumpulan data dilakukan melalui studi dokumen, observasi, dan wawancara untuk mengidentifikasi, mengklasifikasi, serta menginterpretasi kesalahan. Hasil analisis menunjukkan bahwa kesalahan penulisan kata depan merupakan yang paling dominan, diikuti oleh kesalahan pada kata berimbuhan, kata dasar, dan kata ulang. Temuan ini mengindikasikan bahwa peserta didik mengalami kesulitan mendasar dalam membedakan preposisi dan prefiks. Temuan ini berimplikasi pada pentingnya pengembangan bahan ajar yang berfokus pada kesalahan spesifik peserta didik, menyediakan latihan terstruktur, dan mengintegrasikan konteks budaya pembelajar untuk meningkatkan akurasi dan kesadaran berbahasa. Oleh karena itu, diperlukan intervensi pedagogis yang terfokus untuk menjembatani kesenjangan antara penguasaan kosakata dan penerapan kaidah ejaan yang benar. Kata Kunci: bahan ajar; BIPA; karangan deskriptif; kesalahan mengeja; keterampilan menulis